Could calcium hypochlorite and grape seed extract keep the mechanical properties of root dentin and fracture resistance of weakened roots?. (June 2020) - Durigon, M.; Cecchin, D.; de Carli, J.P.; Souza, M. Albino; Farina, A.P.
Abstract: Objectives: To evaluate the effect of different endodontic irrigation protocols on dentin mechanical properties and fracture resistance of roots with 0.5 mm (weakened roots) and 1.5 mm of thickness. Method: Irrigation protocols were the following: Distilled water (DW) + Ethylenediamine tetraacetic acid (EDTA); grape seed extract (GSE) + EDTA; sodium hypochlorite (NaOCl) + EDTA; NaOCl + EDTA + GSE; calcium hypochlorite (Ca(ClO)2 ) + EDTA; Ca(ClO)2  + EDTA + GSE; chlorhexidine (CHX) + EDTA; CHX + EDTA + GSE. The samples were prepared and the values of microhardness, ultimate tensile strength (UTS), and flexural strength were obtained. Further, fracture resistance of roots with dentin thickness of 0.5 mm and 1.5 mm, and restored with fiberglass post relined with composite resin and metal crowns, were evaluated with same irrigation protocols previously described; the failure mode was evaluated as well. All tests presented normality in data distribution (Kolmogorov-Smirnov), and Analysis of Variance and Bonferroni test (α = 0.05) were performed. Results: Higher reduction of dentin microhardness was observed in the NaOCl and NaOCl + EDTA + GSE groups (p < 0.0001). An increased in the UTS values was obtained in the CHX groups (p < 0.0001), while similar values were observed between the control and other groups (p > 0.05). The reduction of dentin flexural strength was observed in the NaOCl groups (p < 0.0001), while no significant changes were observed in the other groups (p > 0.05). With regard to fracture resistance, no statistical difference was obtained among the irrigation's protocols (p > 0.05), except for CHX (p = 0.0031) and CHX + GSE (p = 0.0001) that showed increased in fracture resistance values in roots with 1.5-mm thickness. An increased rate of irreparable failure was obtained in the NaOCl groups, whereas there was a predominance of repairable failure in the other groups. Conclusions: The endodontic irrigation protocol has a significant impact on the dentin mechanical properties; on the other hand, do not reduce the fracture resistance of root with 0.5 mm and 1.5 mm of thickness.